2015
DOI: 10.1016/j.cmi.2015.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression and Chagas disease; experience from a non-endemic country

Abstract: Reactivation of Chagas disease in the chronic phase may occur when immunosuppression is established, sometimes resulting in high parasitaemia and severe clinical manifestations such as meningitis and meningoencephalitis. Although this situation is being increasingly described, there is still scarce information. This retrospective observational study was performed in three Tropical Medicine Units of Barcelona (Spain) included in the International Health Programme of the Catalan Health Institute (PROSICS). The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 30 publications
1
26
1
3
Order By: Relevance
“…The coexistence of CD and immune disorders has been reported worldwide, and may lead to an acute reactivation with parasitemia and severe clinical manifestations such as meningitis and meningoencephalitis (4) (5) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The coexistence of CD and immune disorders has been reported worldwide, and may lead to an acute reactivation with parasitemia and severe clinical manifestations such as meningitis and meningoencephalitis (4) (5) .…”
mentioning
confidence: 99%
“…However, when they were clinically assessed by their doctors (both patients and doctors were aware of test positivity), they did not show any clinical sign that could be attributed to disease reactivation, and cancer remained a treatment priority. It must be noted that immunocompromised individuals with CD were observed for possible disorders related to the presence of the parasite, aiming to provide faster and more effi cient treatment in case of reactivation, since CD can present unusually severe clinical manifestations in immunocompromised patients, such as meningitis and meningoencephalitis (5) .…”
mentioning
confidence: 99%
“…Anti-parasitic treatment during acute phase CD is the central pillar of disease management, partially because of the higher parasite load in comparison with the chronic phase [27][28][29] , in which the etiological treatment has not shown beneficial against cardiopathological progression 30 . Currently, BZL and NFX are the treatment of choice for CD, with BZL being more widely used, owing to its excellent pharmacological efficacy and less adverse effects [31][32][33] . Cancado et al 34 found differences in the proportion of recovered patients treated with BZL for extended periods according to the CD phase; 76% in the acute phase compared with just 8% in the chronic phase.…”
Section: Discussionmentioning
confidence: 99%
“…One case series looked at immunosuppressed patients with chronic CD and included three patients with autoimmune disorders treated with regimens that included biologics. None of these patients suffered a reactivation or severe manifestation of their CD [57]. Although the effect of biological therapies on the course of CD remains unknown, expert opinion favors screening patients with serological testing prior to treatment if their mothers were born in endemic areas, they have lived in endemic areas for prolonged periods, or they have received a blood transfusion in an endemic country [58].…”
Section: Chagas Diseasementioning
confidence: 99%